Enhancing Knowledge And Skills In Arabica Coffee Cultivation: Evidence From Cikidang Village Farmers - Arrizal Alfandira Hendriana Putra; Didit Hadayanti; Randi Sutisna; Reski Ahdani; Sansan (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract Arabica coffee is a strategic commodity with high economic value, yet smallholder farmers in Cikidang Village face challenges in cultivation and harvesting due to limited technical knowledge. This study emphasizes the urgency of improving farmer capacity to sustain productivity and enhance coffee quality. Drawing on human capital, capacity building, and diffusion of innovation theories, the research highlights training as a critical driver of sustainable agricultural development. A qualitative descriptive method was employed, using focus group discussions (FGDs), extension lectures, and field demonstrations with 25 farmers from the Mitra Sejati group. The results show that the technical guidance improved farmers’ knowledge in pruning, fertilization, pest management, and selective harvesting practices. Findings indicate that although ecological conditions support coffee growth, inadequate cultivation and harvesting practices reduce quality. The study concludes that tailored extension programs are effective and replicable models for capacity building in other coffee-producing regions. Keywords: Arabica Coffee, Farmer Capacity, Technical Guidance